Impact of Hyperglycemia on Tear Film and Meibomian Gland Dysfunction: A Cross-Sectional Study - Meng F; Zhou Y; Bao T; Pang Y; Shao Q; Wang L; Zhao J; Li W; Xu H; Yang Y; Zhang B (Diabetes, Metabolic Syndrome and Obesity)
Fanhua Meng,1,* Yuan Zhou,2,* Tong Bao,1,* Yunlei Pang,1 Qinglei Shao,1 Lifeng Wang,1 Jing Zhao,1 Wenchao Li,1 Haiyan Xu,1 Yajun Yang,1,2 Bozhou Zhang1,2 1Department of Retinal, Chifeng Chaoju Eye Hospital, Chifeng, People’s Republic of China; 2Department of Ocular Surface, Baotou Chaoju Eye Hospital, Baotou, People’s Republic of China*These authors contributed equally to this workCorrespondence: Yajun Yang; Bozhou Zhang, Department of ocular surface, Baotou Chaoju Eye Hospital, Baotou, Inner Mongolia Autonomous Region, 014060, People’s Republic of China, Email yangyajun@chaojueye.com; zhangbozhou@chaojueye.comPurpose: Elevated blood glucose levels may disrupt tear film and meibomian gland function, contributing to dry eye disease (DED) and meibomian gland dysfunction (MGD). This study aimed to explore the relationship between hyperglycemia and DED parameters.Methods: A cross-sectional study at Chifeng Chaoju Eye Hospital (June–August 2024) included 56 participants with DED symptoms. Tear meniscus height (TMH), non-invasive tear film breakup time (FNIBUT, ANIBUT), bulbar redness, and meibomian gland atrophy (U-LAMG, L-LAMG) were assessed using a non-invasive ocular surface analyzer. Fasting blood glucose levels stratified patients into high (≥ 7 mmol/l) and normal (< 7 mmol/l) groups, and their association with DED parameters was analyzed.Results: Among 56 patients (mean age 52.5 ± 18.0 years), those with elevated glucose levels (n=28) had more severe DED symptoms (OSDI, p = 0.046), lower TMH, FNIBUT, ANIBUT, and higher bulbar redness scores (all p < 0.05). In contrast, lower glucose levels were associated with greater U-LAMG and L-LAMG atrophy (p < 0.05). Glucose positively correlated with intraocular pressure (IOP), redness, U-LAMG, and L-LAMG but negatively correlated with TMH, FNIBUT, and ANIBUT (all p < 0.05).Conclusion: Hyperglycemia is linked to impaired tear film stability, meibomian gland function, and DED symptoms. Ocular surface disorders in individuals with diabetes may be prevented by effective glycemic control.Keywords: hyperglycemia, dry eye disease, meibomian gland dysfunction, tear meniscus height, non-invasive tear film breakup time